0406 Efficacy of Once-Nightly Sodium Oxybate (ON-SXB; FT218) Across Stimulant Use Subgroups: Post-hoc Analyses From the REST-ON Trial. (25th May 2022) - Thorpy, Michael; Dauvilliers, Yves; Roth, Thomas; Morse, Ann Marie; Roy, Asim; Bogan, Richard; Seiden, David; Dubow, Jordan; Gudeman, Jennifer
Abstract: Introduction: In the REST-ON trial (NCT02720744), once-nightly sodium oxybate (ON-SXB; FT218) was associated with significant improvement vs placebo for mean sleep latency on the Maintenance of Wakefulness test (MWT) and Clinical Global Impression of Improvement (CGI-I) rating in the overall population (both P<0.001) and in subgroups of participants taking concomitant stimulants (both P<0.05). Post-hoc analyses of ON-SXB efficacy on disturbed nocturnal sleep (DNS) and Epworth Sleepiness Scale (ESS) score were conducted. Methods: Participants (≥16 years of age) with narcolepsy type 1 or 2 were randomized 1:1 to ON-SXB (1 week, 4.5 g; 2 weeks, 6 g; 5 weeks, 7.5 g; 5 weeks, 9 g) or placebo. Mixed-effects models for repeated measures calculated P values for change from baseline vs placebo at weeks 3 (6 g), 8 (7.5 g), and 13 (9 g) in ESS score, sleep shifts (ie, number of shifts from N1, N2, N3, and rapid eye movement [REM] sleep to Wake and from N2, N3, and REM sleep to N1), nocturnal arousals (NA), and patient-reported outcomes of sleep quality and refreshing nature of sleep on a 100-point visual analog scale. Results: In the modified intent-to-treat population (n=190), 119 participants took concomitant stimulants (ON-SXB, n=66; placebo, n=53); 71 did not take stimulants (ON-SXB, n=31; placebo, n=40). Improvements with ON-SXB vs placebo were reported: ESS (stimulants: all doses, P≤0.01; no stimulants: 6 g, directional improvement; 7.5 g, P<0.01; 9 g, P<0.001), sleep shifts (stimulants: 6 g, P<0.01; 7.5 and 9 g, P<0.001; no stimulants: all doses P<0.001), NA (stimulants: 6 g, directional improvement; 7.5 g, P<0.01; 9 g, P=0.001; no stimulants: 6 and 7.5 g, P<0.05; 9 g, P=0.01), sleep quality (stimulants: 6 and 7.5 g, P<0.01; 9 g, P<0.05; no stimulants: all doses P<0.001), refreshing nature of sleep (stimulants: 6 and 9 g, P<0.05; 7.5 g, P<0.001; no stimulants: 6 and 7.5 g, P<0.01; 9 g, P=0.001). Conclusion: Data from these post-hoc analyses were consistent with the previously reported results from REST-ON and support the efficacy of ON-SXB for EDS and DNS, as measured by objective and subjective endpoints whether or not stimulants were concurrently used. Support (If Any): Avadel Pharmaceuticals